2019
DOI: 10.1186/s12885-019-5896-6
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term impact of adapted physical activity and diet counseling during adjuvant breast cancer therapy: the “APAD1” randomized controlled trial

Abstract: Background Patients with breast cancer undergoing chemotherapy and radiotherapy experience fatigue and other treatment side effects. Integrative therapies combining physical activity and dietary counseling are recommended; however to date no large randomized controlled trial has been conducted during adjuvant therapy. The Adapted Physical Activity and Diet (APAD) intervention was evaluated for its ability to decrease fatigue (primary outcome), anxiety, depression, body mass index (BMI), and fat ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
137
2
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(161 citation statements)
references
References 76 publications
9
137
2
13
Order By: Relevance
“…Furthermore, several intervention studies support that healthy lifestyle behaviors (maintaining a healthy body weight, engaging in exercise, or consuming a healthy diet) improved cancer survivors' quality of life [6,8,[37][38][39]. The Programme of Accompanying women after breast Cancer treatment completion in Thermal resorts (PACThe) trial also showed that SF-36 physical and mental subscores improved among breast cancer survivors in France who participated in group physical training and nutritional education, yet this improvement was not significant after a year [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, several intervention studies support that healthy lifestyle behaviors (maintaining a healthy body weight, engaging in exercise, or consuming a healthy diet) improved cancer survivors' quality of life [6,8,[37][38][39]. The Programme of Accompanying women after breast Cancer treatment completion in Thermal resorts (PACThe) trial also showed that SF-36 physical and mental subscores improved among breast cancer survivors in France who participated in group physical training and nutritional education, yet this improvement was not significant after a year [6].…”
Section: Discussionmentioning
confidence: 99%
“…In the U.S. intervention study, lifestyle modification interventions regarding nutrition, physical activity, and stress management in cancer survivors (mostly breast, prostate, or skin cancer) improved quality of life [38]. Likewise, the Adapted Physical Activity and Diet (APAD) intervention in patients with early breast cancer improved fatigue and quality of life at the 1 year follow-up [39].…”
Section: Discussionmentioning
confidence: 99%
“…The APAD education program, which was based on the previously published trial method [ 18 ], was implemented during chemotherapy and radiotherapy (26 weeks). The intervention included twice-weekly exercise sessions and six individual nutritional therapeutic education sessions.…”
Section: Methodsmentioning
confidence: 99%
“…The combination of exercise and dietary support has been reported to induce significant weight loss in survivors of early BC (EBC) after adjuvant chemotherapy/radiotherapy [ 13 , 14 , 15 ]. Four randomized controlled trials (RCTs) have assessed the combination of exercise and diet in EBC patients undergoing adjuvant chemotherapy and/or radiotherapy, but they were designed as pilot trials with less than 30 patients in each randomization group [ 16 , 17 , 18 , 19 ]. Therefore, the benefits of an exercise-diet intervention during adjuvant chemotherapy and radiotherapy need to be evaluated in a well-powered and multicenter RCT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation